Vaccinia virus lacking A17 induces complex membrane structures composed of open membrane sheets - Chlanda, Petr; Carbajal, Maria Alejandra; Kolovou, Androniki; Hamasaki, Maho; Cyrklaff, Marek; Griffiths, Gareth; Krijnse-Locker, Jacomine (Archives of virology, 2011)
The vaccinia virus (VACV) precursor membrane, the crescent, consists of an open membrane sheet and is formed by rupture of a cellular compartment. Here, we asked whether A17, a viral membrane protein, plays a role in membrane rupture. Without A17 synthesis, crescents are not formed, and instead, tubular and vesicular membranes accumulate (Rodriguez et al. in J Virol 69:4640-4648, 1). We used electron tomography (ET) to analyze whether the viral membranes lacking A17 consist of open membrane sheets. Tubular, vesicular and so far not described onion-shaped membranes, which consisted of open membrane sheets, were seen. Thus, the data show that membrane rupture occurs independently of the A17 protein.
Gesehen am 28.06.2022